Roles of Third-Party Collection for Accelerating Circular Economy in India - Kalra, Shveta; Hara, Masatoshi (Global journal of Business and Integral Security, 2022)
Various concepts, such as reverse logistics (“RLs”) have been introduced to encourage Circular Economy (“CE”) and Resource Efficiency (“RE”). RLs refers to set of activities needed to collect product. While the EU Directives placed responsibility for ensuring disposal of their End of Life ("EOL")/ End of Use (“EOU”) products on manufacturers, the manner and responsibility of collection is still unclear. Resultantly, collection of waste products specially electrical products have not attained the level, as was expected. RE regulations in India are at nascent stages and are designed on principles of EU Directives. Collection is primarily driven by Indian government and the informal sector. The success of RE is essentially based on level of collection rates. Collection rates can be accelerated by putting an infrastructure conducive for collection. This paper studies the role of third party collectors for the purpose of accelerating CE and RE, for a developing country like India.